Associations of Serum Mineral levels of Copper, Magnesium and Calcium with Skeletal Muscle mass and Strength in Chinese children, aged 6-11: A Cross-Sectional Study - Abubakar Tarawally; Zheqing Zhang (Health Dynamics, 2024)
Skeletal Muscle mass (SMM) and strength are important parameters used in determining children’s health throughout their stages of development and through adulthood. Similar to its properties in adulthood and aging, low skeletal muscle mass and strength contribute to adverse health outcomes in childhood, several pieces of research have described an increased risk of developing metabolic dysfunction and cardiovascular diseases in children and adolescents with low skeletal muscle mass and strength[1-3]. Several macro-and micro minerals are involved in maintaining healthy skeletal muscles and strength from childhood through to adulthood. Copper (Cu), magnesium (Mg), and calcium (Ca) are essential for the normal development of the skeleton [4]. Copper serves as an important trace element vital to the health of all living organisms and collagen, which is the main structural material in bone. Copper deficiency can lead to fractures, skeletal abnormalities, and osteoporosis quite recently, the relevance of loss of skeletal muscle mass or strength to bone health has been recognized, with evidence of associations between low skeletal muscle mass, low strength, or low physical performance and outcomes of osteoporosis [5, 6]. Serum copper concentrations were reported to have a positive correlation with BMD of the lumbar spine as measured using dual-energy X-ray absorptiometry and quantitative computerized tomography in premenopausal female [7], copper serum level was also reported to have a positive correlation with bone density at total hip and spine in postmenopausal women [8].